Perdas de grãos na colheita mecanizada de soja e desenvolvimento de aplicativo para dispositivos móveis - Souza, Daniel Ciro de (2023)
Soybean cultivation has increased significantly in recent years, and harvesting is carried out mechanically, but this stage has a high operational planning cost. With this in mind, the aim of this study is to determine grain losses in mechanized soybean harvesting and to develop an application for mobile devices to aid decision-making in harvest planning. The work was carried out on rural properties in Rio Grande do Sul central region state. Losses in mechanized harvesting were measured using 0.56 cm metal hoops and a bifactorial statistics was used for the first experiment, with five speeds 3.0, 4.0, 5.0, 6.0 and 7.0 km h-1 and two platform driver types (draper and helical); the second experiment analyzed the track system (axial and hybrid), with four replications in a bifactorial statistics, analyzing on platform losses, internal mechanisms and total losses. The treatments means were compared at a 5% probability level using Tukey test; the application was developed in the Dart programming language, which was created by Google using the Flutter framework. The results showed that there were significant differences in relation to platform conductor type, with the draper having lowest losses. For the track system, hybrid system also had lowest losses. The experiments showed that as the working speed increases, so do the losses in mechanized soybean harvesting. And the application can be an important tool for helping farmers and technicians make decisions, with a view to planning and managing mechanized soybean harvesting.